Pharmacists' Roles and Factors Affecting Patient Care in Korea - Monica J. Hwang; Henry N. Young (University of Minnesota Libraries Publishing, 2015)
Objectives: This study was conducted to explore Korean community pharmacists' perceptions of their roles in providing care to patients after the implementation of the Separation of Prescribing and Dispensing Act (SPD Act) and to investigate pharmacists' perceptions about factors that impact their patient care. Methods: Eight community pharmacists participated in semi-structured, face-to-face, in-depth interviews in Korea. A snowball sampling technique was used to obtain participants. Interviews were audio-recorded and transcribed. Interviews were analyzed using a summative content analysis procedure. Key findings: Participants' perceptions of their roles centered on dispensing prescriptions, educating and counseling patients, and helping patients with OTC products. Participants perceived time constraints due to prescription volume and patient expectations as factors influencing their provision of patient care. Conclusion: This study suggests that the SPD Act was successful in changing pharmacists' roles in the Korean health care system. None of the participants perceived their role to include prescribing, while all of the participants indicated that their primary role was to dispense medications. Future research should examine the pervasiveness of the themes identified in this study across Korean community pharmacy practice in order to generalize the impact of the SPD Act.   Type: Original Research